INTEGRATING FRUGAL INNOVATION AND VALUE CO-CREATION FOR SUSTAINABLE DEVELOPMENT - Hermann Nodari, Cristine; da Silva, Carolline Candeias; Schmidt, Serje; da Silva, Fábio; Alessandra Silva, Ananery (Revista Gestão Organizacional, 2025)
Purpose: This study aims to explore the intersection between frugal innovation, value co-creation, and sustainable development. Method/approach: Through a systematic literature review following PRISMA guidelines, the analysis covered 53 articles published between 2011 and 2023 to identify emerging patterns. Main findings: Five key elements were identified as essential to this synergy: customer orientation, sustainability, operational efficiency, flexibility and adaptability, and empowerment. Theoretical, practical/social contributions: The research highlights the positive outcomes of frugal innovation and value co-creation across various sectors, such as healthcare and sustainable tourism, contributing to the Sustainable Development Goals (SDGs). Originality/relevance: The findings suggest that integrating these elements provides competitive advantages, including enhanced customer satisfaction through value co-creation, strengthened corporate image through sustainable innovation, and increased profitability through adaptation and innovation. The study concludes by outlining avenues for future research, emphasizing the potential of these approaches to foster sustainable development in diverse contexts.